Hubungan antara tingkat pengetahuan ibu tentang asi eksklusif dengan praktik pemberian asi eksklusif pada bayi usia 0-6 bulan di wilayah kerja puskesmas jenggot kota pekalongan - Suryo Pratikwo; Millatin Puspaningtyas; Dyah Retno Sukmaningrum (JURNAL LITBANG KOTA PEKALONGAN, 2017)
Improvement of human quality should start as early as possible that since she was a baby. One factor that has an important role is the provision of breastfeeding, because it provides protection against various infectious diseases. There are several factors that affect the practice of exclusive breastfeeding in infants aged 0-6 months include the knowledge level of mothers, family support, and the role of health personnel. In this research using descriptive correlation research design whose purpose is to find a picture of the relationship between mother’s level of knowledge about practice of exclusive breastfeeding to exclusive breastfeeding in infant aged 0-6 months in which the approach used is a cross sectional. A population of 410 using a sample 41 respondents, through by simple random sampling technique. The results showed that the respondents have good knowledge of as many as 20 people (48.8%), but exclusive breastfeeding is only 7 people (17.1%) means that many respondents did not give exclusive breastfeeding. Statistical test used were Spearman Rank and the results obtained p value = 0.004 (? = 0.05) (p value